2012
DOI: 10.1002/jclp.20861
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processes Mediate the Relation Between Mindfulness and Social Anxiety Within a Clinical Sample

Abstract: Further research using a longitudinal design and other measures of mindfulness is needed to replicate these findings and further explicate the mechanism by which mindfulness might be associated with negative cognitive appraisals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
3
22
0
1
Order By: Relevance
“…These strengths notwithstanding, the present study also had limitations. Although cross-sectional designs are commonly used to explore mediation hypotheses (e.g., Schmertz, Masuda, & Anderson, 2012), cross-sectional studies cannot be used to infer causal relationships between variables, and future studies should extend our results using longitudinal designs. In addition, the present study examined a young, predominantly female student sample, which may limit the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 87%
“…These strengths notwithstanding, the present study also had limitations. Although cross-sectional designs are commonly used to explore mediation hypotheses (e.g., Schmertz, Masuda, & Anderson, 2012), cross-sectional studies cannot be used to infer causal relationships between variables, and future studies should extend our results using longitudinal designs. In addition, the present study examined a young, predominantly female student sample, which may limit the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, one study found that probability and cost biases partially mediated the relation between mindfulness and social anxiety among individuals with social phobia using a cross-sectional design (Schmertz, Masuda, & Anderson, 2012). That is, the relation between mindfulness and social anxiety was explained through relations to cognitive biases.…”
Section: Introductionmentioning
confidence: 99%
“…Other mediating variables may play a role in this scenario. For example, Schmertz found that rumination was a mediating variable between mindfulness and social anxiety in clinical population (31). This may have affected the results, meaning that students' ruminations may have affected the correlation between the intensity of cognitive fusion and social interaction anxiety.…”
Section: Discussionmentioning
confidence: 99%